2009
DOI: 10.1111/j.1365-2664.2009.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained predation effects of hatchery‐reared transgenic coho salmon Oncorhynchus kisutch in semi‐natural environments

Abstract: Summary1. The potential risks of accidental or intentional introduction of transgenic organisms to nature are unknown. We have previously shown that, after being reared in the hatchery, growth hormone transgenic coho salmon Oncorhynchus kisutch can exert a stronger predation effect on natural prey under simulated natural conditions compared with hatchery-reared genetically wild conspecifics. However, when reared in a simulated natural environment, the difference between the two genotypes was greatly reduced.2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…), whereas older GM fish appears to retain their hatchery phenotype even after being in a stream‐like environment for several months (Sundström et al . ; Sundström, Lõhmus & Devlin ), (ii) number and frequency of escapes as repeated ‘trials’ increase the chance that at least some escaped individuals will be successful (McGinnity et al . ; Kolar & Lodge ), (iii) longevity and dispersal ability of escaped individual (Sundström et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), whereas older GM fish appears to retain their hatchery phenotype even after being in a stream‐like environment for several months (Sundström et al . ; Sundström, Lõhmus & Devlin ), (ii) number and frequency of escapes as repeated ‘trials’ increase the chance that at least some escaped individuals will be successful (McGinnity et al . ; Kolar & Lodge ), (iii) longevity and dispersal ability of escaped individual (Sundström et al .…”
Section: Discussionmentioning
confidence: 99%
“…The only direct assessment of the impact of GM fish on other species has been through quantification of predation effects (Sundström et al . ) where GM salmon reared in the hatchery consumed more prey than non‐GM reared in the hatchery, but compensatory growth responses in prey resulted in final biomass among prey being similar across predator treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, previous studies assessing growth-related survival under predation (including strains transgenic for growth hormones) were based on unknown numbers of families and parents (Biro et al 2004;Sundström et al 2004;Biro and Post 2008), similar numbers of families (four to five; Sundström et al 2009), more than five (not further specified; Sundström and Devlin 2011), or partly higher numbers of families (49 wild versus five domesticated; Vandersteen et al 2012). However, none of these studies reported to have accounted for family effects by either balancing sample sizes among families or by statistically assessing family effects on survival, although possible effects were discussed by Vandersteen et al (2012).…”
Section: Survivalmentioning
confidence: 99%
“…At this time, size differences among strains were already present. For individuals beyond the fry stage, different methods have been used to adjust body sizes between strains by using unreported methods (Biro et al 2004;Biro and Post 2008), individuals at different ages (Sundström et al 2009), matched sizes (Fleming and Einum 1997), or both the latter two in comparison ). We decided against using size-matched individuals, as in our case respective individuals from the upper or lower tail of strain size distributions are unlikely to be representative.…”
Section: Survivalmentioning
confidence: 99%
“…Such plasticity associated with foraging/growth/predation risk tradeoffs have likely evolved to maximize fitness in nature (Dill ), and can be sustained even when environments change (Sundström et al. ).…”
Section: Discussionmentioning
confidence: 99%